Persepsi Mahasiswa Terhadap Penggunaan Software Geogebra Sebagai Multimedia Pembelajaran Matakuliah Kalkulus Multivariabel - Nurul Arfinanti (Tadris Matematika IAIN Palopo, 2018)
This study aims to determine students' perceptions of the use of multimedia learning software GeoGebra in Multivariable Calculus course. Students' perceptions of the use of media or multimedia learning are closely related to their achievement. Media or multimedia learning in accordance with the desire of students will make them motivated. This research is qualitative data analysis was done descriptively. The data obtained in this study comes from researchers as the main instrument, the data questionnaire and interview data is unstructured. The results are students' perceptions of the use of multimedia learning software GeoGebra in Multivariable Calculus courses are in the positive category.